Design and control properties of arrangements for distillation of four component mixtures using less than N-1 columns - Mendez-Valencia, D. M. (Array, 2008)
Summary: The design and study of dynamic properties of distillation sequences using side-stream columns with less than N-1 columns for separation of four-component mixtures were studied. Total annual cost and dynamic properties (using singular value decomposition) were used to compare properties of arrangements with less than N-1 columns to base cases with three columns (conventional case). Quaternary feeds containing four hydrocarbons were analyzed. For systems with low concentrations of one component in the feed, side-stream cascades often show significantly lower operating, capital costs and best dynamic properties compared to the base cases. Low purity requirements also favor side-stream cascades. Some rules are presented to predict which sequence will have the lowest energy consumption capital cost and better dynamic properties